2021
DOI: 10.1002/anie.202102327
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure In Situ Single‐Crystal X‐Ray Diffraction Reveals Turnstile Linker Rotation Upon Room‐Temperature Stepped Uptake of Alkanes

Abstract: The rare availability of suitable single-crystal X-ray diffraction (SCXRD) structural data allows for the direct interpretation of the response of af ramework to gas sorption and mayl ead to the development of improved functional porous materials.W er eport an in situ SCXRD structural investigation of af lexible MOF subjected to methane,e thane, propane,a nd butane gas pressures.S upporting theoretical investigations indicate weak host-guest interactions for the crystallographically modelled gaseous guests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…On the other hand, adaptability is a hallmark of enzymes. Flexible cavitins mimic these owing to structural changes that accompany adsorption and desorption steps (Heerden et al, 2021). Cavitins are able to create chiral molecular catalysts via preferential secondary interactions between the substrate and framework that induce enantioselectivities not achievable in homogenous systems.…”
Section: Metallocavitins As Bioinspired Catalystsmentioning
confidence: 99%
“…On the other hand, adaptability is a hallmark of enzymes. Flexible cavitins mimic these owing to structural changes that accompany adsorption and desorption steps (Heerden et al, 2021). Cavitins are able to create chiral molecular catalysts via preferential secondary interactions between the substrate and framework that induce enantioselectivities not achievable in homogenous systems.…”
Section: Metallocavitins As Bioinspired Catalystsmentioning
confidence: 99%
“…Metal−organic frameworks (MOFs), inorganic−organic hybrid porous materials with tuneable properties, have been explored for various applications. 20,21 These can also be promising candidates as fluorescent and electrochemical sensors due to the feasibility of placing fluorescent linkers and metal/ligand redox centers inside the framework. MOFs have been explored for sensing of diverse analytes, 22−24 but there is only a handful of reports on nicotine detection using MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, many researchers explored electrochemical sensing of nicotine using glassy carbon electrodes (GCE), carbon paste electrodes, and pencil graphite electrodes as unmodified electrodes. Numerous composites have been prepared as electrochemical sensors using conducting materials such as graphene, multiwalled carbon nanotubes, metal oxides, nanoparticles, nanotubes, and polymers. Such sensors, despite their better current sensitivities, involve tedious sample preparations. Metal–organic frameworks (MOFs), inorganic–organic hybrid porous materials with tuneable properties, have been explored for various applications. , These can also be promising candidates as fluorescent and electrochemical sensors due to the feasibility of placing fluorescent linkers and metal/ligand redox centers inside the framework. MOFs have been explored for sensing of diverse analytes, but there is only a handful of reports on nicotine detection using MOFs. Recently, our group has also investigated MOFs for fluorescence and electrochemical sensing applications. , Encouraged by our recent findings, we have designed the first MOF-based dual sensor for nicotine detection.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of porous materials, often we observed that, once the solvent molecules are removed from the lattice, it loses its crystal singularity, leading to a poor or no diffraction pattern in single-crystal X-ray diffraction (SCXRD) analysis . So, it has been always a challenge to obtain fully desolvated forms of porous compounds using SCXRD analysis . In addition even after full desolvation, some porous materials, when exposed to an open environment or air, tend to show affinity toward moisture adsorption from the atmosphere/air .…”
Section: Introductionmentioning
confidence: 99%
“…8 So, it has been always a challenge to obtain fully desolvated forms of porous compounds using SCXRD analysis. 9 In addition even after full desolvation, some porous materials, when exposed to an open environment or air, tend to show affinity toward moisture adsorption from the atmosphere/ air. 10 Such cases, especially where the sample preparation needs exposure to an open environment or air even for a very small period of time, often lead to the wrong interpretation of the data.…”
Section: ■ Introductionmentioning
confidence: 99%